Effect of organic matter and ionic strength and soil texture on positive ions in the soil extracted search - Faten Abdel Reda Dakel; Abdul Karim Hassan Hudhafa; Ashraf Mohmmed Sheriff (Zien Journals, 2023)
The overall concentration of mineral salts in the water extracted from the soil is referred to as salinity, and an increase in salinity presents a problem for the plant. The salt buildup in the ground can be traced back to a few different sources (groundwater, irrigation water, and unfair agricultural practices resulting from man from excessive chemical fertilization). Because it disperses soil particles and aggregates, which causes a decrease in water conductivity, poor aeration, and an increase in the bulk density of the soil, the sodium ion is considered one of the essential and dependent ions in the process of determining the quality of irrigation water. This is due to its effect on chemical properties, as an increase in its concentration in irrigation water directly affects salinity. In addition, the sodium ion's effect on some of the soil's physical The soil's interaction with other ions, such as chlorides, carbonates, and bicarbonates, results in the formation of a variety of salt compounds, all of which contribute to the process of salinizing the soil. Therefore, the research assumes that washing the soil or using organic conditioners will minimize the number of salts and sodium in the soil (organic matter). In addition, the significance of incorporating organic matter into the soil in order to boost output while simultaneously enhancing the soil's physical and chemical characteristics The purpose of this research is to investigate the factors that influence the total number of positively charged ions in the soil, including ionic strength, soil texture, and organic matter.
Keywords: including; positively; characteristics; organic